2018
DOI: 10.1126/scisignal.aar3250
|View full text |Cite
|
Sign up to set email alerts
|

Engineering allosteric regulation in protein kinases

Abstract: Phosphoregulation – in which the addition of a negatively charged phosphate group modulates protein activity – is a common feature of proteins that enables dynamic cellular responses. To understand how new phosphoregulation might be acquired, we mutationally scanned the surface of a prototypical yeast kinase (Kss1) to identify potential regulatory sites. The data reveal a set of spatially distributed “hotspots” that coevolve with the active site and preferentially modulate kinase activity. By engineering simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Allostery is an intrinsic property of all proteins: all protein surfaces 13 are potential allosteric sites subject to ligand binding or to mutations that may introduce structural perturbations elsewhere in the protein 14 , 15 . Drugs targeting allosteric sites could offer improved selectivity compared with traditional active-site targets 16 , 17 , and allosteric pathways can be engineered to regulate protein functions 18 21 . We posited that dynamic couplings in atomic motions are related to protein structure and sought to predict allosteric coupling based solely on established protein structures with the goal of building maps of dynamic coupling in proteins without the use of expensive computational or experimental approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Allostery is an intrinsic property of all proteins: all protein surfaces 13 are potential allosteric sites subject to ligand binding or to mutations that may introduce structural perturbations elsewhere in the protein 14 , 15 . Drugs targeting allosteric sites could offer improved selectivity compared with traditional active-site targets 16 , 17 , and allosteric pathways can be engineered to regulate protein functions 18 21 . We posited that dynamic couplings in atomic motions are related to protein structure and sought to predict allosteric coupling based solely on established protein structures with the goal of building maps of dynamic coupling in proteins without the use of expensive computational or experimental approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Other possibilities to achieve this include the engineering of allosterically regulated proteins. Pincus et al recently demonstrated the feasibility of modifying proteins in order to make their activity dependent on phosphorylation by a specific protein kinase [93] . By using protein kinase A (PKA) as the regulator, they have already shown how the activation of an endogenous signaling pathway can be rewired to the allosteric activation of proteins from different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of LOV2 insertion site was guided by Statistical Coupling Analysis (SCA), an approach for analyzing coevolution between pairs of amino acids across a homologous protein family [22][23][24]. A central finding of SCA is that co-evolving groups of amino acids, termed sectors, often form physically contiguous networks in the tertiary structure that link allosteric sites to active sites [24][25][26]. To create the DL121 fusion, Lee et al followed the guiding principle that sector connected surface sites in DHFR might serve as preferred sites (or "hot spots") for the introduction of allosteric regulation [20].…”
Section: Characterization Of An Unoptimized Allosteric Fusion Of Dhfrmentioning
confidence: 99%